KETERLIBATAN SELEBRITI SEBAGAI POLITISI: PENGUATAN PARTAI POLITIK ATAU PENGGALANGAN SUARA - Khamimiya, Aza Rifda; Fauzi, Agus Machfud; Affandi, Mochamad Arif (Universitas Tribhuwana Tungga Dewi, 2023)
Ahead of the general election, there are more and more celebrities to enter politics. This phenomenon becomes a social reality in society when the democratic party takes place. This research seeks to discuss the rationality of parties determining celebrities as candidates for legislation and to find out the existence of celebrities in political party institutions. This research method is descriptive qualitative with case study method. The research subject is Verrell Bramasta's membership in the National Mandate Party. The data were obtained through document studies from online news and also audio-visual recordings from Narasi Newsroom and Metro Tv. To complete the data obtained by library research through e-books, and journals relevant to research. To strengthen this research, the researcher uses an analytical knife with Max Weber's theory of rationality and Bourdue's capital. The results obtained show that the National Mandate Party is cooperating with celebrities because of social capital ownership. Party rationality makes candidates for legislators based on electoral figures. Celebrities are believed to have influence, power, popularity which can influence the party in increasing the electability of the party. Through empowering this capital, it is the main goal of the National Mandate Party to be able to defend the acquisition of parliamentary seats in the 2024 election contestation later, not because of strengthening political party institutions because the joining of celebrities is nothing but because of the persona they have.Menjelang pemilihan umum kian marak selebriti untuk terjun ke dunia politik. Fenomena ini menjadi sebuah realitas sosial di tengah masyarakat ketika pesta demokrasi berlangsung. Penelitian ini berupaya untuk membahas mengenai rasionalitas partai menentukan selebriti sebagai calon legislasi dan untuk mengetahui keberadaan artis pada kelembagaan partai pilitik. Metode penelitian ini adalah kualitatif deskriptif dengan metode studi kasus. Subjek penelitian adalah ketergabungan Verrell Bramasta pada Partai Amanat Nasional. Data diperoleh melalui studi dokumen dari berita online dan juga audio-visual rekaman dari Narasi Newsroom dan Metro Tv. Untuk melengkapi data diperoleh dengan studi kepustakan melalui e-buku, dan jurnal relavan dengan penelitian. Untuk memperkuat penelitian ini, peneliti menggunakan pisau analisis dengan teori rasionalitas Max Weber dan modal milik Bourdue. Hasil yang diperoleh bahwa Partai Amanat Nasional mengandeng selebriti tidak lain karena kepemilikan modal sosial. Rasionalitas partai menjadikan calon legislator berdasarkan electoral figure. Selebriti diyakini memiliki pengaruh, kekuasaan, popularitas yang dapat menginfluancer partai dalam meningkatkan elektabilitas partai. Melalui pemberdayaan modal tersebut menjadi tujuan utama Partai Amanat Nasional untuk dapat mempertahakan perolehan kursi parlemen pada kontestasi pemilu 2024 nanti bukan karena memperkuat kelembagaan partai politik sebab gabungnya selebriti tidak lain karena persona yang dimiliki.